2016
DOI: 10.1016/j.meatsci.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applying preslaughter feed withdrawal at the abattoir on behaviour, blood parameters and meat quality in pigs

Abstract: To study the effects of starting time of feed withdrawal on behaviour during loading and lairage, and meat quality (pH, colour and drip loss) in pigs, a total of 700 pigs were distributed into two groups. One group (FARM) was fasted for 18 h at the farm before transport and for 6 h before slaughter (including 2 h transport and 4 h lairage), while for the other group (PLANT) fasting time started at the departure from the farm (2 h transport plus 22 h lairage). Total fasting time was 24 h before slaughter for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
2
29
0
1
Order By: Relevance
“…In an epidemiological study conducted in Canada, farm was identified as the major source (25%) of deadson-arrival (DOA) and nonambulatory pigs on arrival at the plant compared with the transporter and the packer (16% each; Sunstrum et al, 2006;Dewey et al, 2009). The main sources of variation of these effects between farms include: the housing system (Barton-Gade, 2008;Rocha et al, 2016), the preparation of pigs for transport (Faucitano et al, 2010;Dalla Costa et al, 2016), and the handling of pigs at loading (Johnson et al, 2013;Goumon and Faucitano, 2017).…”
Section: Farm Of Originmentioning
confidence: 99%
See 2 more Smart Citations
“…In an epidemiological study conducted in Canada, farm was identified as the major source (25%) of deadson-arrival (DOA) and nonambulatory pigs on arrival at the plant compared with the transporter and the packer (16% each; Sunstrum et al, 2006;Dewey et al, 2009). The main sources of variation of these effects between farms include: the housing system (Barton-Gade, 2008;Rocha et al, 2016), the preparation of pigs for transport (Faucitano et al, 2010;Dalla Costa et al, 2016), and the handling of pigs at loading (Johnson et al, 2013;Goumon and Faucitano, 2017).…”
Section: Farm Of Originmentioning
confidence: 99%
“…Feed withdrawal is a recommended practice for on-farm preparation of pigs before slaughter in order to prevent animal losses and travel sickness during transport (Bradshaw et al, 1996;Averós et al, 2008;National Farm Animal Care Council, 2014), to reduce carcass contamination due to lower risk of gut contents spillage during carcass processing, and to improve pork quality (Faucitano et al, 2010). However, when compared with unfasted pigs, fasted groups of pigs (18 h prior to loading) appear to be more difficult to handle at loading, as they go backward, roundturn, and vocalize more (Dalla Costa et al, 2016). The increased frustration, fatigue, and excitement caused by hunger are the likely causes for these behaviors (Arnone and Dantzer, 1980;Lewis, 1999;Edwards et al, 2010b).…”
Section: Feed Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the LC muscle consists predominantly of red fibers, which are an indicator of dark, firm, and dry (DFD) meat. Variations of pH 45 have multifactorial causes such as the hottest season of the year, fights between animals that did not fast, and type of muscular fiber (Dalla Costa et al, 2016;Rey-Salgueiro et al, 2018). Due to these factors, the pH decline in the transformation of muscle into meat directly influences attributes such as color, WHC, softness, and flavor, according to Rübensam (2000), Gomide (2007), and Scheffler et al (2013); thus meat should not be classified using a single parameter.…”
Section: Discussionmentioning
confidence: 99%
“…However, the LC muscle consists predominantly of red fibers and is used as an indicator of dark, firm, and dry (DFD) meat. Variations of pH45 have multifactorial causes such as the hottest season of the year, fights between animals that did not fast, and type of muscular fiber(Dalla Costa et al, 2016;Rey-Salgueiro et al, 2018). Due to these factors, pH decline in the transformation of the muscle in meat directly influences attributes such as color, WHC, softness, and flavor, according toRübensam (2000); Ramos;…”
mentioning
confidence: 99%